Potencial e custois de produção de hidrogênio eletrolítico no Brasil junto às usinas de açúcar e álcool - Halmeman, Maria Cristina Rodrigues (2008)
The object of this project was to verify the potential for the hydrogen production via water electrolysis by using the exceeding electrical energy resulting from the cogeneration process in alcohol and sugar plants. The studies were made from July to November/2007 in plants authorized by the ANEEL that use the sugar cane bagasse as fuel for the generation of thermal and electrical energy. The data were taken from each plant. The processing history of sugar cane for the last five years was verified and the calculations were made based on the values of the 2006/2007 harvest. The operation time of the plants was considered to be 202 days in average. The amount of sugar cane processed daily and the total of bagasse produced, electrical energy generated in a year and exceeding electrical energy were calculated for each plant. Along with the cost of the electrolysers, it was also obtained the energy consumption average value of 5.2 kWh to produce 1 Nm3 of hydrogen and a specific cost for the electrolysis plant that ranges from US$ 1,555 kW-1 to US$ 2,510 kW-1. The hydrogen production costs regarding the capacity of hydrogen production range from US$ 0.50 Nm-3 to US$ 0.75 Nm-3. The results show an increasing potential for the generation of exceeding electrical energy that can be used for the production of electrolytic hydrogen, since the costs for hydrogen production presented themselves to be similar to the ones found in other studies carried out, however, using other energy sources.